MODERNITY AND KERALA’S VASTHUVIDYA TRADITION - Jose, Jaison (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Modernity and modernization emerged in Europe, transforming all aspects of life. Modernity has made a significant leap in the field of knowledge, leading to a radical transformation in all human affairs. The ideas of European modernity were introduced to India and Kerala through the colonial education project. As a result, we examined the ancient knowledge project of Vasthuvidya through the lens of scientific logic inherited from European modernity. Consequently, Vasthu Shastra has been labeled as a pseudoscience lacking scientific basis. However, we are currently experiencing a period where the limitations of the anthropocentric view promoted by modernity are being exposed. The new paradigm challenges modernity and its paradigmatic projects. The new premises have sparked widespread discussion about Kerala's Vasthuvidya tradition and associated concepts as an alternative to modern architectural styles. This article explores how modernity's worldview has perceived our Vasthuvidya and the relevance that the new environment has brought to our architectural heritage.